Horse Racing in Imperial Rome: Athletic Competition, Equine Performance, and Urban Spectacle. Issue 3 (3rd March 2020) - Bell, Sinclair W.
Abstract: Chariot races were the earliest, most popular, and longest-lived of all forms of 'spectacles' in the Roman world. This essay surveys the spatial and architectural framework of the Circus Maximus, the primary chariot racing venue at Rome, and circuses around the empire; the organization of the races, including the role of the factions; the symbolic representations of victories and athletic victors, as well as the charioteers' actual prizes; and the horses that were bred for racing. Throughout I also briefly discuss the sport's spectators and fans, for whom the sport was a socially binding religion. The essay focuses on the first through the fourth centuries A.D., with the bulk of the evidence (literary, epigraphic, artistic, and archaeological) drawn from the first two centuries. In keeping with current directions in the study of ancient sport and spectacle, the approach adopted here places less emphasis on the legal and technical aspects of the chariot races ('event-oriented sport history') and more on these competitions as 'part of a broader social canvas' (the 'social history of sport and spectacle').